Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: Developing the performance of public education departments in the Kingdom of Saudi Arabia in light of strategic management Ms. Mashael Asir Al-Otaibi., Ms. Jawaher Khalid Al-Yousef. ,Ms. Haifa Khalif Al-Maalawi The reality of applying entrepreneurial leadership in secondary schools in Jeddah from the teachers’ point of view Mr. Abdulrahman Hamid Al-Sala The Impact of The Digital Story in the Development of some Life Skills among Children with Autism in A Human Development Center in Al-Qassim Ms. Faten Marzouq Meznan The Role of Artificial Intelligence Applications in Developing Vocational Education; A Future Vision for Professional Training Ms. Asma Thabet M. Alorfi., Ms. Maha Ouda Awad Alharbi Mindfulness as a predictor of impulsive behavior among female high school students in Jeddah, Saudi Arabia Ms. Nojod Melfi Alharbi Challenges Related to Children Faced by Kindergarten Teachers of Children with Autism Spectrum Disorder in Improving Their Quality of Life Ms. Rajaa Ebrahim Nassar The Perceptions of Yemeni Universities Students towards Practical Training and Internships in Translation Programs Ms. Azhar Abdulrahman Raweh, Prof. Mohammad Abdu Al-Mekhlafi